2019
DOI: 10.32602/jafas.2019.6
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Factors Influencing Bank Profitability: Evidence from the West African Economic and Monetary Union Banking Sector

Abstract: This paper investigates the factors that influence bank profitability. Using static and dynamic panel data techniques, a sample of 86 banks from eight countries making up the West African Economic and Monetary Union over the period 2006-2014 is utilized. framework, the size effect is investigated for both determinants of profitability and CAR models, while the time effect is incorporated in the dynamic framework. In regards to the determinants of bank profitability, the results show evidence of significant eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…The significant effect agrees with Msomi (2022), Kohlscheen et al (2018). It however contradicts findings by Shamshur and Well (2019) and Adalessossi and Erdoğan (2019).…”
Section: Summary Of Findingscontrasting
confidence: 64%
“…The significant effect agrees with Msomi (2022), Kohlscheen et al (2018). It however contradicts findings by Shamshur and Well (2019) and Adalessossi and Erdoğan (2019).…”
Section: Summary Of Findingscontrasting
confidence: 64%
“…Finally, a more recent study by Adalessossi and Erdogan (2019), using a dataset of 86 banks from eight countries from the West African Economic and Monetary Union over the period 2006-2014, examined bank specific, industry specific and macroeconomic factors that affect bank's profitability. Bank-specific factors examined include measures related to capital, liquidity, efficiency, asset quality and bank size.…”
Section: Literature Review and Hypothesis De-velopmentmentioning
confidence: 99%
“…For example, Hoffmann (2011) examined the determinants of the profitability of the US banks and he showed a negative relationship between the capital ratio and bank's profitability. On the other hand, Zhang and Dong (2011) and Adalessossi and Erdogan (2019), found that there is a positive association between capital ratio and profitability, whereas Pasiouras, Tanna, & Zopounidis (2008) find that stricter capital requirements improve bank's cost efficiency but decrease its profit efficiency. Beyond capital ratio, researchers also examined the relationship between financial institution's size and profitability.…”
Section: Introductionmentioning
confidence: 99%